DAMPAK PENGEMBANGAN WISATA PANTAI TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT PESISIR - Ahmad Raihan; Fendy Oktavianus (Riset Sains dan Teknologi Kelautan, 2023)
Coastal communities are residents who live and carry out socio-economic activities related to coastal and marine resources. Thus, narrowly coastal communities have a relatively high dependence on the potential and conditions of origin of coastal and oceanic power. Their condition is very related to using how the state of origin of the power around them. The majority of people in coastal areas of Indonesia are engaged in the profession as fishermen who have been inherited from previous generations. Coastal communities have diverse socio-economic activities, ranging from farming, trading, and fishing. However, coastal people tend to work as fishermen. This activity results in the origin of aquatic resources in the sea as the main target of the community to meet the needs of life, both meeting family consumption needs and for commercial. The economic activities of coastal residents tend to work as fishermen. In addition to being faced with directly using their resources in the sea, fishermen have been hereditary among coastal communities. The purpose of writing this time is to find out how the activities of coastal residents in the socio-economic aspects of the people. The development of coastal tourism can also affect social change in coastal communities. Beach tourism can broaden people's horizons and knowledge about culture, environment, and sustainability. The impact of coastal tourism development on the socioeconomic conditions of coastal communities can vary depending on various factors, such as good management, community participation, and sustainability of tourism development.